IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH UNTUK MENINGKATKAN BRAND IMAGE DI SMAN 1 BESUKI - Rifqoni Maulanal Qodri; Abdurrahman Abdurrahman (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the implementation of School-Based Management (MBS) to enhance the brand image at Besuki State Senior High School 1. The study employs a qualitative approach using a case study design. Data were collected through observation, interviews, and documentation involving the principal, teachers, the school committee, and relevant stakeholders. The results indicate that the implementation of MBS to enhance the brand image was carried out through three main stages. First, MBS planning is carried out in a participatory manner by involving stakeholders in the development of the school’s vision, flagship programs, performance targets, and communication strategies. Second, MBS implementation is realized through the execution of flagship programs and school communications to strengthen the institution’s identity and reputation. Third, MBS evaluation has a positive impact on increasing public trust, strengthening the school’s reputation, and boosting student interest. This success is supported by the principal’s leadership, teachers’ commitment, stakeholder support, and consistent flagship programs, although there are still some obstacles such as limited resources and competition among institutions. This study confirms that effective MBS implementation can be a key strategy for building and strengthening a school’s brand image.